Academic Support Coordinator - Tsaousi, Christiana (My University, 2026)
2024-2025: Coordinated and hosted a distinguished guest speaker event with Dr. Lucy Gill-Simmen from Royal Holloway, University of London, who delivered a talk on the use of AI in teaching and learning. Supported the Academic Support Team in developing an AI Guide to inform the university’s institutional AI policy. Designed and launched the “Ακαδημαϊκο καταφύγιο” sessions, aimed at providing dedicated support and a safe space for staff.